The Official Indonesian Qurʾān Translation The History and Politics of Al-Qur'an dan Terjemahnya - Lukman, Fadhli (The Global Qur'an, 2022)
This book studies the political and institutional project of Al-Qur'an dan Terjemahnya, the official translation of the Qurʾān into Indonesian by the Indonesian government. It investigates how the translation was produced and presented, and how it is read, as well as considering the implications of the state's involvement in such a work. Lukman analyses the politicisation of the Qurʾān commentary through discussion of how the tafsīr mechanism functions in this version, weighing up the translation's dual constraints: the growing political context, on the one hand, and the tafsīr tradition on the other. In doing so, the book pays attention to three key areas: the production phase, the textual material, and the reception of the translation by readers. This book will be of value to scholars with an interest in tafsīr studies, modern and Southeast Asian or Indonesian tafsīr sub-fields, the study of Qurʾān translations, and Indonesian politics and religion more broadly.